La poesia personale e corale di Mario Benedetti (ENTHYMEMA, 2020)
Mario Benedetti proposes a poetry where the poet’s voice is extremely personal and choral at the same time: the reader gets the impression of a ballad, or of a story narrated in the past during evening rural gatherings. However, the inner voice is always there: this voice becomes a colloquial function which lets the ego outstand. The cohesion and the textual architecture are granted by an impersonal repetitive style or by an outstanding subjectivity. The poetry ends by a way back, a nostos: the essential research is about a place, a vital space which survives, at least in the memory.
Keywords: Benedetti; subjectivity; orality; repetitive style; Italian contemporary poetry